Modern concepts in pavement engineering delegate information : Friday 17 May 1996, One Great George Street Conference Centre, the Institution of Civil Engineers, London. (Thomas Telford series of the Institution of Civil Engineers' Seminar., 1996)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a seminar held on 17 May 1996.